The effect of an inhibitor of gut serotonin (LP533401) during the induction of periodontal disease - Lima, G M G; Corazza, B J M; Moraes, R. M.; de Oliveira, F. E.; de Oliveira, L. D.; Franco, G C N; Perrien, D. S.; Elefteriou, F.; Anbinder, A. L. (My University, 2016)
BACKGROUND AND OBJECTIVE: LP533401 is an inhibitor of tryptophan hydroxylase 1, which regulates serotonin production in the gut. Previous work indicates that LP533401 has an anabolic effect in bone. Thus, we hypothesized that inhibition of gut serotonin production may modulate the host response in periodontal disease. In this study, we aimed to analyze the effects of LP533401 in a rat periodontitis model to evaluate the role of gut serotonin in periodontitis pathophysiology. MATERIAL AND METHODS: Twenty-four rats were divided into three groups: treated group (T: ligature-induced periodontal disease and LP533401, 25ï¿½mg/kg/d) by gavage; ligature group (L: ligature-induced periodontal disease only); and control group (C: without ligature-induced periodontal disease). After 28ï¿½d, radiographic alveolar bone support was measured on digital radiographs, and alveolar bone volume fraction, tissue mineral density and trabeculae characteristics were quantified by microcomputed tomography in the right hemi-mandible. Left hemi-mandibles were decalcified and alveolar bone loss, attachment loss and area of collagen in the gingiva were histologically analyzed. RESULTS: Significant difference between the L and C groups was found, confirming that periodontal disease was induced. We observed no difference between the T and L groups regarding alveolar bone destruction and area of collagen. CONCLUSION: LP533401 (25ï¿½mg/kg/d) for 28ï¿½d does not prevent bone loss and does not modulate host response in a rat model of induced periodontal disease.
Keywords: bone; enterochromaffin cells; periodontitis; serotonin